Elucidating the reaction mechanism of SnF2@C nanocomposite as a high-capacity anode material for Na-ion batteries - Ali, Ghulam; Lee, Ji-Hoon; Oh, Si Hyoung; Jung, Hun-Gi; Chung, Kyung Yoon (ELSEVIER SCIENCE BV, 2017)
Sn-based materials have drawn great attention as anodes for rechargeable batteries because of their extremely high theoretical energy storage capacities. Herein, a nanocomposite based on SnF2 and acetylene black is proposed as a high-performance anode material for sodium-ion batteries and their electrochemical performances, as well as related energy storage mechanism, are investigated. The nanocomposite electrode delivered a high reversible capacity of 563 mAh g(-1) which is considerably improved compared to a reversible capacity of 323 mAh g(-1) of the micron-sized bare SnF2 electrode. The nanocomposite electrode shows superior rate capability and delivers a reversible capacity of 191 mAh g(-1) at a high current density of 1 C, while the bare electrode delivers negligible capacities. The changes in crystallographic structure are observed using in-situ XRD and the results reveal the existence of a solid solution of two or more species during dis/charging. The electronic and atomic configurations depending on the state of dis/charging are systematically investigated using ex-situ X-ray absorption spectroscopy. The results reveal that the valence change of Sn follows the conversion (SnF2 + 2Na -> Sn + 2NaF) and alloying (Sn + XNa -> SnNaX) reaction upon sodium insertion into a composite.
Keywords: ELECTRICAL ENERGY-STORAGE; SODIUM-ION; CATHODE MATERIALS; LI-ION; ELECTROCHEMICAL PROPERTIES; LITHIUM; TIN; ELECTRODES; NANOCRYSTALS; PERFORMANCE